PIMPINAN LEMBAGA PENDIDIKAN ISLAM VISIONER DAN ORIENTASI TOTAL QUALITY - Khotibul Umam, Aguswan (JURNAL TARBAWIYAH, 2014)
Every leader of Islamic educational institution is demanded to have sharp and deep vision, value, and norm. Therefore, his staffs can regularly adapt and follow the change of age. It suggests that the role of progressive leader is very crucial for that process. Another demand is that the leader must be able to realize his leadership vision and mission through his rational and operational work program.Operationally, the implementation of progressive leadership in Islamic educational institution is by creating quality culture and total quality. The orientation and actualization quality culture can be acquired through the implementation ofÂ  progressive leadership in Islamic education institution.Â Key word: Leader, Institution, Islamic Education, Orientation, Total QualityÂ